"Gynaecological malignancies complicating pregnancy: a review". (16th November 2010) - Halkia, E; Stefanatou, G; Spaliaras, D; Pateraki, E; Mylona, C; Akrivos, N; Vorgias, G
Abstract : Objective: To review the existing evidences regarding the management of pregnancy associated malignancies. Materials and Methods: The authors conducted a literature search of MEDLINE/PUBMED database. The authors used the keywords "gynaecological cancers", "pregnancy", "malignancies", "treatment", "prognosis". The authors obtained additional studies from reference lists of retrieved articles. Results: Endometrial cancer can be diagnosed during pregnancy, incidentally in cases of spontaneous abortion. Before pregnancy, fertility sparing treatment with progestagones is used for a well-differentiated stage IA. During pregnancy, a surgical treatment should be offered. Women with cervical cancer >24 weeks, have an early CS and a hysterectomy. Women <12 weeks pregnant start treatment immediately. Second trimester diagnosis poses a treatment challenge. Ovarian cancer can be treated with surgery at an early stage. Adnexectomy and omentectomy are performed early in pregnancy. If more advanced, surgery should be followed by chemotherapy. Conclusion: The management of patients with a malignant tumor during pregnancy depends on the type, the stage of the tumor, and the term of the pregnancy.